Evaluation of visual outcomes and patient satisfaction after implantation of a diffractive trifocal intraocular lens. Issue 2 (February 2016) - Mendicute, Javier; Kapp, Alexander; Lévy, Pierre; Krommes, Gero; Arias‐Puente, Alfonso; Tomalla, Mark; Barraquer, Elena; Rozot, Pascal; Bouchut, Pierre
Abstract : Purpose : To evaluate clinical outcomes after the implantation of a diffractive trifocal intraocular lens (IOL). Setting : Nine European ophthalmology centers. Design : Prospective noncomparative interventional multicenter study. Methods : The trifocal diffractive AT LISA tri 839MP IOL was implanted in eyes with bilateral cataract. Monocular and binocular visual performance was assessed as was the level of perceived photic phenomena, patient satisfaction, and spectacle dependence 1 month and 3 months postoperatively. Results : The IOL was implanted in 208 eyes of 104 patients. The mean binocular uncorrected distance visual acuity improved from 0.44 logMAR ± 0.30 (SD) to 0.02 ± 0.10 logMAR and 0.03 ± 0.09 logMAR at 1 month and 3 months, respectively ( P < .01). The mean binocular uncorrected intermediate visual acuity (80 cm) improved from 0.51 ± 0.30 logMAR to 0.09 ± 0.13 logMAR and 0.10 ± 0.15 logMAR at 1 month and 3 months, respectively ( P < .01). The mean binocular uncorrected near visual acuity improved from 0.67 ± 0.31 logMAR to 0.16 ± 0.14 logMAR and 0.15 ± 0.14 logMAR, respectively ( P < .01). Among the more frequently perceived photic phenomena were halos; however, approximately 75% of patients were not bothered by them. More than 90% of patients were satisfied with the outcome. Spectacle independence at all distances was higher than 90%. Conclusion : This IOL provided excellent visual outcomes and high refractive predictability at all distances, including intermediate, leading to high levels of patient satisfaction and spectacle independence. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.